THE EFFECT OF PROFITABILITY, LIQUIDITY, AND LEVERAGE ON FIRM VALUE WITH DIVIDEND POLICY AS INTERVENING VARIABLE (Case Study on Finance Sector In Indonesian Stock Exchange 2016-2020 Period) - Ranti Damayanti; Agus Sucipto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Abstract: The purpose of this study aims to examine the effect of profitability, liquidity, and leverage on firm value of dividend policy as an intervening variable. This have a look at uses quantitative methods by collecting secondary data, specifically financial statements and annual reports of companies in the financial sector listed on the Indonesia Stock Exchange (IDX). The sampling technique used purposive sampling and obtained a total sample of 26 companies. This study uses path analysis using the SmartPLS 3.3.3 statistical tool. The results of the study prove that profitability has a negative and insignificant effect on dividend policy, liquidity has a negative and significant effect on dividend policy, leverage has a positive and significant effect on dividend policy, profitability has a positive and significant effect on firm value, liquidity has a negative and significant effect on firm value, leverage has a positive and significant on firm value, dividend policy has a negative and insignificant effect on firm value, dividend policy is not able to mediate profitability on firm value, liquidity has no direct effect on firm value through dividend policy, dividend policy has an indirect effect of leverage on firm value in the financial sector listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Keywords: Profitability, Liquidity, Leverage, Dividend Policy, Firm Value